2021
DOI: 10.1177/09749306211024433
|View full text |Cite
|
Sign up to set email alerts
|

Foreign Direct Investment and Growth Nexus: Further Evidence from Africa’s Largest Economy

Abstract: The study investigated the effect of foreign direct investment (FDI) on economic growth in Nigeria, which is currently Africa’s largest economy, and also determined the long-run relationship between FDI and economic growth in Nigeria from 1981 to 2017. The study adopted the autoregressive distributed lag modelling approach and ordinary least square in the analysis. The empirical results revealed that FDI has a positive and significant relationship with economic growth in Nigeria within the period under review.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 15 publications
(7 citation statements)
references
References 22 publications
(14 reference statements)
2
5
0
Order By: Relevance
“…In addition, FDI can help boost exports by expanding the capacity and competitiveness of domestic production. This result is consistent with the findings of multiple studies (Mehic et al, 2013;Alvarado et al, 2017;Hayat, 2017;Sultanuzzaman et al, 2018;Dinh et al, 2019; http://journal.uinjkt.ac.id/index.php/signifikan https://doi.org/10.15408/sjie.v12i1.29975 Shittu et al, 2020;Zeeshan et al, 2020;Mohamed et al, 2021;Nasir et al, 2021;Orji et al, 2021;Ahmad et al, 2022), which have found that an increase in FDI inflows can stimulate economic growth. In addition, Raza et al (2021) discovered that countries with high institutional quality tend to have stronger economic growth and more foreign direct investment (FDI) inflows.…”
Section: Resultssupporting
confidence: 91%
See 1 more Smart Citation
“…In addition, FDI can help boost exports by expanding the capacity and competitiveness of domestic production. This result is consistent with the findings of multiple studies (Mehic et al, 2013;Alvarado et al, 2017;Hayat, 2017;Sultanuzzaman et al, 2018;Dinh et al, 2019; http://journal.uinjkt.ac.id/index.php/signifikan https://doi.org/10.15408/sjie.v12i1.29975 Shittu et al, 2020;Zeeshan et al, 2020;Mohamed et al, 2021;Nasir et al, 2021;Orji et al, 2021;Ahmad et al, 2022), which have found that an increase in FDI inflows can stimulate economic growth. In addition, Raza et al (2021) discovered that countries with high institutional quality tend to have stronger economic growth and more foreign direct investment (FDI) inflows.…”
Section: Resultssupporting
confidence: 91%
“…Meanwhile, others have found no evidence or weak evidence of such an effect. Orji et al (2021) found that FDI can increase economic growth, and therefore governments should aim at attracting FDI in all sectors, particularly the industrial and service sectors. This result is supported by the findings of Ahmad et al (2022), who observed that FDI could drive economic growth.…”
Section: Introductionmentioning
confidence: 99%
“…(2) Resident consumption level (HC): Based on the work of Bao et al [57], the total retail sales of social consumer goods per capita was selected as a proxy variable for resident consumption level, and the price deflator was used to adjust the total retail sales of social consumer goods before calculating the per capita result. (3) Regional openness (RO): Based on the work of Orji et al [58], the actual use of foreign direct investment in each region was used as a measure. (4) Technological innovation capability (TI): Based on the work of Shi et al [59], the full-time equivalent of R&D personnel was selected as a proxy variable for technological innovation capability.…”
Section: Other Control Variablesmentioning
confidence: 99%
“…Open economies with skilled labour force and prospects for profitable growth tend to attract massive FDI than closed and highly regulated economies (Mold, 2003;OECD, 2002). There are different forms of FDI; where creating a joint venture, mergers, and acquisitions, establishing a subsidiary company by building new facilities, and reinvesting proceeds earned from their investment (Orji et al, 2021). FDI has been recognized not only as one of the channels of capital formation but also as a source of advanced technology, technical know-how, employment creation, and access to new markets (Forte & Moura, 2013).…”
Section: Introductionmentioning
confidence: 99%